RUMAH PANJANG SEBUAH WANTAH INTEGRASI MASYARAKAT SUKU DAYAK KALIMANTAN - Imam Hindarto (Naditira Widya, 2008)
The spatial layout in a longhouse may depict community-integrity of its dwellers. Spatial management in a Dayak longhouse is generally based on a macrocosmic balance between natural and cultural environment;spatial division is set up upon a philosophical value to uphold spatial sacredness and everything that represent it. Such spatial management is further carried out by exercising a philosophical order and discipline upon the dwellers, which will then create regulation-abiding-individual and manageable social control and construction.